The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s40661-017-0058-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial experience with CA4P anticancer therapy: focus on efficacy, cardiovascular adverse events, and hypertension management

Abstract: Combretastatin A4-phosphate (CA4P) is a vascular-disrupting agent (VDA) in clinical development for the treatment of ovarian and other cancers. In contrast to antiangiogenic agents, such as bevacizumab, which suppress the development of new tumor vasculature, VDAs target established tumor vasculature. These differing but complementary mechanisms of action are currently being explored in clinical trials combining CA4P and bevacizumab. Clinical experience to date has highlighted an important need to better under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
83
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 34 publications
(80 reference statements)
0
83
0
1
Order By: Relevance
“…In contrast, oral CKD‐516 was not associated with hypertension, which was the only DLT observed in the intravenous CKD‐516 trial . Notably, oral CKD‐516 demonstrated no significant cardiovascular adverse events that are observed with other VDAs …”
Section: Discussionmentioning
confidence: 92%
“…In contrast, oral CKD‐516 was not associated with hypertension, which was the only DLT observed in the intravenous CKD‐516 trial . Notably, oral CKD‐516 demonstrated no significant cardiovascular adverse events that are observed with other VDAs …”
Section: Discussionmentioning
confidence: 92%
“…CA4P, a water-soluble prodrug of CA4, is used as a vasculardisrupting agent for the treatment of ovarian, glioma, non-small cell lung cancer (NSCLC), pancreatic neuroendocrine tumors, and etc. (Grisham et al, 2018). CA4P monotherapy is well tolerated, and most adverse events during cancer treatment are mild to moderate in intensity.…”
Section: Discussionmentioning
confidence: 99%
“…Some preclinical and clinical studies have reported the e cacy and safety pro les of VDAs [12][13][14][15][16]. In theory, radiation therapy is not effective at locally controlling hypoxic areas in tumor tissues.…”
Section: Introductionmentioning
confidence: 99%